A Chinese patent medicine, Shexiang Baoxin Pill, for Non-ST-elevation acute coronary syndromes: A systematic review. (24th December 2016) - Zhou, Zhou; Shen, Weixing; Yu, Lili; Xu, Cong; Wu, Qibiao
Abstract: Ethnopharmacological relevance: Shexiang Baoxin Pill (SXBXP) is a well-known Chinese patent medicine, widely used for Non-ST-elevation acute coronary syndromes (NSTE-ACS). It is composed of seven materia medicas or extracts (Moschus, Radix Ginseng, Calculus Bovis, Cortex Cinnamomi, Styrax, Venenum Bufonis and Borneolum Syntheticum). Aim of the study: This study is aimed to systematically review the relevant randomised controlled trials (RCTs) to determine the efficacy and safety of SXBXP for long-term management of NSTE-ACS. Materials and methods: A systematic review and meta-analysis were carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: The PRISMA Statement. All randomised controlled trials (RCTs) comparing long-term Shexiang Baoxin Pill with conventional treatment, with outcome measures relating to efficacy and safety were selected. Primary clinical outcome was the risk of cardiovascular events, secondary outcomes were hospitalizations, angina symptoms, electrocardiogram (ECG) measurements, and adverse events. Results: Eleven RCTs recruiting 1389 patients were included, the overall risk of bias of the included trials is high and the quality poor. Compared with conventional treatment alone, long-term Shexiang Baoxin Pill plus conventional treatment might be more effective in lowering the risk of cardiovascular events (RR=0.36, 95% CI 0.26–0.49, <0.00001), hospitalizations (RR=0.38, 95% CI 0.21–0.67, P =0.0009), and improving angina symptoms (RR=1.19, 95% CI 1.13–1.26, P<0.00001), ECG measurements (RR=1.25, 95% CI 1.13–1.39, P<0.00001). Overall rate of adverse events was not elevated (P=0.43). Conclusions: From the available evidence, SXBXP added to conventional treatment may have beneficial effects on the long-term outcomes of NSTE-ACS, without serious adverse events. However, given the high risk of bias and low quality of the included trials, currently, there is no adequate evidence to draw any conclusions about its routine use. Large, methodologically-sound trials are needed to further assess its effects. Graphical abstract: